ANALISIS KUALITATIF KANDUNGAN SAKARIDA DALAM TEPUNG DAN PATI UMBI GANYONG (Canna edulis Ker.) - Kusbandari, Aprilia (Pharmaciana, 2015)
Canna Tubers (Canna edulis Ker.) is one of the plants producing carbohydrates. ItsÂ  also contains of protein, fat, vitamins, minerals,Â  phosphorus, iron and more calciums. The purpose ofÂ  this study is to identify ofÂ  sugarÂ  in the powder and starch from canna tuber is a hydrolysis and didnât hydrolysis. The method of qualitative analysis with tube testÂ  andÂ  Thin Layer Chromatography (TLC). The result indicated that before hydrolysisÂ  canna powderÂ  gaveÂ  sucrose (Rf = 0.45) and mannose (Rf=0.51), while after hydrolysis it gaveÂ  glucose (Rf=0.44), fructose (Rf=0.61) and mannose (Rf=0.51). In addition, canna starch gaveÂ Â  glucose (Rf=0.44) and maltose (Rf=0.35).